1990
DOI: 10.14198/ingeo1990.08.07
|View full text |Cite
|
Sign up to set email alerts
|

El cultivo de la uva de mesa en el Medio Vinalopó: recursos hídricos y riegos localizados de alta frecuencia

Abstract: RESUMENAridez y escasez de recursos hídricos han propiciado la existencia en el Vinalopó Medio de una extensa superficie regada, sometida a la explotación de acuíferos subterráneos. La ampliación descontrolada del cultivo de la uva de mesa unida a un irracional uso del agua, comprometen la propia viabilidad económica del sector agrario en la zona. La utilización de sistemas de riego localizado de alta frecuencia y la ampliación de la capacidad de embalse, forman parte de un proceso de renovación y una posible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Those results showed root intrusion affected the SDI system's uniformity and yield. This was agreed with Ferguson [11], Pizarro Cabello [8], and Ayars [2].…”
Section: Spring Wheat Yield and Qualitysupporting
confidence: 91%
See 1 more Smart Citation
“…Those results showed root intrusion affected the SDI system's uniformity and yield. This was agreed with Ferguson [11], Pizarro Cabello [8], and Ayars [2].…”
Section: Spring Wheat Yield and Qualitysupporting
confidence: 91%
“…Rubens et al [7] measured the intrusion of coffee and citrus roots into 14 different emitter models placed in containers and found that all the tested emitters experienced root intrusion. Root intrusion is an important factor that affects SDI system uniformity and life span, as well as crop yields [2,8,9].…”
Section: Introductionmentioning
confidence: 99%